2018
DOI: 10.1038/sj.bdj.2018.220
|View full text |Cite
|
Sign up to set email alerts
|

Teaching stress management in undergraduate dental education: are we doing enough?

Abstract: Dentistry is recognised as a stressful profession. A number of studies focusing on undergraduate education have shown high levels of stress in dental students. However, despite calls to do so, little has been published on methods to teach future dental professionals about stress and how to manage it on a personal level. Psychological stress which is uncontrolled may have an effect on general health. It is recognised, however, that stress can be beneficial if channelled appropriately. Techniques and ways to tea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 19 publications
0
12
0
1
Order By: Relevance
“…Some work has been done to improve dental students' learning environment, like teaching stress management in the UK and mindfulness in Germany . Studies from India and Turkey suggested that spiritual health/religion may increase students' coping strategies .…”
Section: Introductionmentioning
confidence: 99%
“…Some work has been done to improve dental students' learning environment, like teaching stress management in the UK and mindfulness in Germany . Studies from India and Turkey suggested that spiritual health/religion may increase students' coping strategies .…”
Section: Introductionmentioning
confidence: 99%
“…[17] Stress management is another area that is often overlooked in the undergraduate curriculum. [18] This should be included in the curriculum as well as pre-internship orientation to help the interns to cope with their mental strengths and to balance professional as well as personal life in this phase of transition. Basic life support, Humanities, interpersonal skills, ethics, and stress management are topics that should be included in the medical undergraduate curriculum, as expressed by interns in our study.…”
Section: Discussionmentioning
confidence: 99%
“…wskazują, że studenci II, a następnie IV roku stomatologii mieli najwyższy poziom niepokoju i stresu [35], co może wiązać się z różnicami programowymi. Studenci V roku doświadczają zarówno stresorów związanych ze szkoleniem na kierunku lekarsko-dentystycznym, jak i stresorów związanych z ich przyszłą pracą jako lekarzy z pełną odpowiedzialnością za opiekę nad pacjentem [36][37][38]. Co więcej, zaobserwowaliśmy, że największym zmartwieniem studentów I i V roku w naszym badaniu było to, że nie będą w stanie opanować całej puli wiedzy medycznej oraz fakt, iż postrzegali studia medyczne bardziej jako zagrożenie aniżeli wyzwanie.…”
Section: Dyskusjaunclassified